Interpersonal metadiscourse in persuasive journalism: A study of texts by American and Iranian EFL columnists - Noorian, Mina; Biria, Reza (Journal of Modern Languages, 2017)
Interpersonal metadiscourse refers to aspects of a text which reflect the writer’s position towards both the content in the text and the reader. This study aimed to explore the role of interpersonal metadiscourse markers in persuasive writing. For this purpose, two elite newspapers in the United States and Iran, The New York Times and Tehran Times respectively, were chosen. Based on a textual analysis of 12 opinion articles (6 from each newspaper), this investigation intended to find out whether American and Iranian EFL writers employed the same amounts of interpersonal markers (hedges, certainty markers, commentaries, attitude markers, and attributors) in their texts. The findings revealed that interpersonal metadiscourse was present in both sets of data, but that there were significant differences between the two groups regarding the occurrences of interpersonal markers, specifically in the case of commentaries. The results suggested that different factors interacted in the choice of metadiscourse markers in newspaper opinion articles written by American and Iranian EFL columnists: culture-driven preferences, genre-driven conventions, and Iranian EFL writers’ extent of foreign language experience. The study also stressed the need for more contrastive studies in the area of metadiscourse and more attention to this important element in L2 writing courses.